Smoke-free cafe in an unregulated European city: highly welcomed and economically successful. Issue 3 (4th September 2003) - Künzli, N; Mazzoletti, P; Adam, M; Götschi, T; Mathys, P; Monn, C; Brändli, O
Abstract : Objective: In a unique setting with two identical cafes, which only differed in their smoking ordinances, this study assessed the influence of smoking policies on the choice of the cafe, investigated regulatory preferences among customers, and evaluated the claim that smoking cafes have better sales performance in a city without smoking bans. Methods: In a parallel assessment, customers of both cafes answered a questionnaire. Sales were compared and air pollutants were measured to confirm air quality differences. Results: The two customer groups (n = 177) differed only with regard to smoking status (p < 0.01). The smoking regulation was the most often cited selection criterion (83%). In the non-smoking café, 89% indicated that they were usually annoyed by smoke in coffee houses, and 62% would avoid or leave cafes for this reason. Two thirds stated that all cafe/restaurants should offer the opportunity of a smoke-free environment. However, almost half stated that mandatory regulations are not needed and that customers should make individual arrangements based on tolerance and courtesy. Those who were informed about the health effects of secondhand smoke were more likely to call for clear policies. Whereas sales showed no differences, tips were 22% (p < 0.001) higher in the non-smoking cafe. Conclusion: In a generation raised in smoking friendly environments, customers paradoxically ask for a landmark shift towards smoke-free opportunities, while substantially adhering to the tobacco industry paradigm of promoting "tolerance" rather than smoke-free policies. Given the clear preference of a large number of customers, hospitality businesses could, however, greatly profit from offering smoke-free environments even in the absence of regulatory policies.